2021
DOI: 10.1002/ppap.202100054
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced transmembrane transport of reactive oxygen species by electroporation effect of plasma

Abstract: Recently, plasma has been proposed as a new efficient tool for various biological and medical applications. The function of plasma is mainly realized through two aspects: Electric field and reactive species. However, because the interactions between plasma and cells are quite complicated, the synergistic effect of electric field and reactive species has not been studied in depth. In this paper, the synergetic effects of electric field and transportation of reactive species on cells are investigated by a two‐di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…This disruption facilitates the entry of highly active RONS into the interior of the virus, enhancing the effectiveness of plasma oxidation. [ 35 ]…”
Section: Mechanism Of Cap In Viral Inactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…This disruption facilitates the entry of highly active RONS into the interior of the virus, enhancing the effectiveness of plasma oxidation. [ 35 ]…”
Section: Mechanism Of Cap In Viral Inactivationmentioning
confidence: 99%
“…By influencing their behavior, the electric field can enhance or guide the disinfection process. Yang et al [ 35 ] found that electroporation induced by the plasma field can promote the transmembrane transport of plasma RONS.…”
Section: Mechanism Of Cap In Viral Inactivationmentioning
confidence: 99%
“…The optical emission spectrum (OES) shown in Figure 4 indicated that the OES of atomic oxygen at O (3s 5 S-3p 5 P) 777 nm and O (3p 5 4p-3p 5 6s) 844 nm increased by about 40% as the O 2 ratio increased from 0 to 0.1% and decreased by 63.3% as the O 2 percentage increased from 0.1% to 1% [22,23]. Energetic electrons with electron energy >10 eV are needed to generate the excited atomic oxygen corresponding to the OES at 777 nm and 844 nm [22,[24][25][26]; therefore, the concentration of atomic oxygen in the ground state was much higher than that in the excited state [27,28]. For example, the absolutely calibrated TALIF measurement of atomic oxygen in the grounded state in the effluent of the similar argon plasma jet indicated that the atomic oxygen density was in the order of 10 15 /cm 3 , and that it decreased with the distance to the nozzle by up to an order of magnitude [29].…”
Section: Characteristics Of Ltp Jet Arraymentioning
confidence: 99%
“…Simulations show that the discharge of the plasma scalpel in the water-vapor layer (50% H 2 O and 50% H 2 vapor mixture) generates a large number of reactive species, with H atoms being the most abundant (approximately 400 ppm), followed by O atoms (20 ppm) and OH (3–10 ppm). The rate constant of the OH radical extraction of H is about 5000 times faster than that of H atom and 500 times faster than that of the ground state oxygen atom [ 4 , 38 , 39 , 40 , 41 , 42 ]. The experimental spectral data show that a large number of hydroxyl radicals generated by the plasma scalpel [ 4 ] can achieve oxidative etching of tissue [ 43 , 44 , 45 , 46 ].…”
Section: Oxidation Effect Of Plasma Scalpelmentioning
confidence: 99%